Facile synthesis of highly tunable monodispersed calcium hydroxide composite particles by using a two-step ion exchange reaction. Issue 23 (3rd April 2020) - Yang, Chih-Hui; Wang, Ya-Chin; Wang, Ta-Chen; Chang, Yi-Ching; Lin, Yun-Chul; Chen, Pei-Fan; Huang, Wei-Jie; Wen, Hsin-Yi; Lin, Yu-Mei; Kuo, Wen-Shuo; Wang, Yi-Ting; Huang, Keng-Shiang
Abstract : The synthesized Ca(OH)2 composite particles were size tunable, had a spherical shape, and were monodisperse. Abstract : "Calcium hydroxide [Ca(OH)2 ]" is a medicament frequently used for antimicrobial purposes in endodontic procedures, or it is used as a toxic-waste adsorbent in industry. Ca(OH)2 particles produced through conventional methods are size untunable and have a wide size distribution and polygonal shape. In this paper, a novel and facile approach involving template-mediated synthesis and two-step ion exchange is proposed for uniform size Ca(OH)2 composite particles generation. "Sodium-alginate (Na-alginate)" was used as a precursor, and monodisperse Na-alginate emulsions were formed through needle droplet or droplet microfluidic technology. After the first ion exchange step with the Ca 2+ ions, "calcium-alginate (Ca-alginate)" particles were obtained. The Ca-alginate particles were intermediate reaction products and were designed to be the templates for ensuring the spherical shape and size of products. The OH − ions were used for the second ion exchange step to fabricate Ca(OH)2 composite particles. The results revealed that the Ca(OH)2 composite particles were size tunable, had a spherical shape, and were monodisperse (with a relative standard deviation of less than 8%). The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay revealed that the Ca(OH)2 composite particles were potential biocompatible materials.